Evaluation of job performance: An empirical study of different KDS characters - Zheng, W.B.; Kau, S.; Huai, L.M. (2009)
Intellectual property and intellectual capital became the critical components of wealth creation, and core employees of organization become more significant than ever. Especially, key employees with higher organizational performance characteristics are often entitled talent for their core networking status in creating the organizational intelligent capital values. In the field of talents' retention, empirical study of relationship-oriented between talents' performance and withdraw tendency by modeling is taking lead way in highlighting the talents' turnover mechanism. This study will integrate positive research from talents' organizational performance characters through standard of Key degree scale (KDS) in MBA samples from China to compare the significance and functional routes which are reflected by various talent retention factors, to reveal retention management policy which may influence talent retention and performance decision-making.